Withaferin A inhibits osteosarcoma cells through inactivation of Notch-1 signalling (Bangladesh Journal of Pharmacology, 2014)
Human osteosarcoma cells were treated with withaferin A and the antiproliferative activity was evaluated by the 3-(4, 5 dimethyl-thiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assays. Real-time RT-PCR and western blot were used to investigate whether the down-regulation of Notch-1 contributes to withaferin A-induced inhibition of proliferation in osteosar-coma cells. The results showed that withaferin A caused marked inhibition of osteosarcoma cell growth and G2?M phase cell cycle arrest. This was associated with concomitant attenuation of Notch-1 and down-regulation of its downstream genes, such as matrix metalloproteinases. These results suggest that antitumor activity of withaferin A is mediated through a novel mechanism involving inactivation of the Notch-1 signalling pathway. Our data provide the first evidence that the down regulation of Notch-1 by withaferin A may be an effective approach for the treatment of osteosarcoma.